Effects of Voltage-Gated K+ Channel on Cell Proliferation in Multiple Myeloma - Wei Wang; Yuying Fan; Shuye Wang; Lianjie Wang; Wanting He; Qiu Zhang; Xiaoxia Li (The Scientific World Journal)
Objective. To study the effects and underlying mechanisms of voltage-gated K+ channels on the proliferation of multiple myeloma cells. Methods. RPMI-8226 MM cell line was used for the experiments. Voltage-gated K+ currents and the resting potential were recorded by whole-cell patch-clamp technique. RT-PCR detected Kv channel mRNA expression. Cell viability was analyzed with MTT assay. Cell counting system was employed to monitor cell proliferation. DNA contents and cell volume were analyzed by flow cytometry. Results. Currents recorded in RPMI-8226 cells were confirmed to be voltage-gated K+ channels. A high level of Kv1.3 mRNA was detected but no Kv3.1 mRNA was detected in RPMI-8226 cells. Voltage-gated K+ channel blocker 4-aminopyridine (4-AP) (2 mM) depolarized the resting potential from −42 ± 1.7 mV to −31.8 ± 2.8 mV (P<0.01). The results of MTT assay showed that there was no significant cytotoxicity to RPMI-8226 cells when the 4-AP concentration was lower than 4 mM. 4-AP arrested cell cycle in G0/G1 phase. Cells were synchronized at the G1/S boundary by treatment of aphidicolin and released from the blockage by replacing the medium with normal culture medium or with culture medium containing 2 mM 4-AP. 4-AP produced no significant inhibitory effect on cell cycle compared with control cells (P>0.05). Conclusions. In RPMI-8226, voltage-gated K+ channels are involved in proliferation and cell cycle progression its influence on the resting potential and cell volume may be responsible for this process; the inhibitory effect of the voltage-gated K+ channel blocker on RPMI-8226 cell proliferation is a phase-specific event.